An Investigation On The Use Of Strategy - Based Game To Learn Bidayuh Culture - Clement, Jimel (2016)
An Investigation on the use of Strategy-Based Game to learn Bidayuh Culture. Online computer game is an effective edutainment tool to educate game players on contents namely culture and history. Unlike the generation of the yesteryears, today's young generation of users are techies and device oriented. This gradually shaped their lifestyle, learning behaviour and eventually their motor-skill resulting from repetitive interaction with screen devices. Subsequently, users as such tend to display rather low tolerance on conventional learning materials like books and adopt individualistic lifestyle. This research stemmed from the problem that is the absence of documentation on Bidayuh culture in computer game. The research focuses on designing a strategy-based game, which narrate the story of a Bidayuh warrior as case study. The objective is to propose and design online game to engage young generation of gamers to learn Bidayuh culture and to investigate its viability as a tool in documenting and learning this culture. The research methodology comprises of quantitative research, experimental research and online survey. The experimental research were conducted by developing the prototype and tested among the online respondents via the email link that was distributed to them